Kecemburuan pada Laki-laki dan Perempuan dalam Menghadapi Perselingkuhan Pasangan Melalui Media Internet - Asriana, Widya; Ratnasari, Yudiana (Universitas Muria Kudus, 2012)
Research on the type of infidelity that causes jealousy in men and women show consistent results, namely that men are more jealous of sexual infidelity in the face of a partner than women, whereas women are more jealous in the face of emotional infidelity than male partners. Infidelity through the internet a threat to the relationship to the individual in modern times now. Therefore, this study find out about the differences of men and women in the face of emotional infidelity and sexual partner through internet media. This hypothesis was tested using a forced-choice dilemmas in which participants (N = 168) were asked to choose the type of infidelityis more cause of jealousy: emotional or sexual. The results show that in the face of a partner´s infidelity via the Internet media, both men and women were significantly more jealous in dealing with emotional infidelity than sexual infidelity. Women, when compared with men, more jealous partner in dealing with emotional infidelity, but there were no significant differences between male and female partner´s sexual infidelity in the face.The results of this study will be discussed in the context of the theory ofevolutionary psychology. This important study carried out in order to arise the awareness that the relationship over the Internet can provide a serious effect on relationships in the real world.